Students’ Knowledge Comprehension after Implementation of Live Conventional Demonstration, Video Teaching and Video-Assisted Instruction Methods in Endodontic Practice - Mohammadzadeh Akhlaghi, Nahid; Khalilak, Zohreh; Vatanpour, Mehdi; Moshari, Amirabbas; Ghaffari, Saman; Namazikhah, Mohammad Sadegh (Iranian Endodontic Journal, 2017)
Introduction: Video-assisted clinical instruction (VACID) has been found to be a beneficial teaching tool for various fields in dentistry. The aim of this interventional study was to compare the efficacy of live conventional demonstration (CD), video teaching, and VACID (video with explanation) methods in teaching of root canal treatment to undergraduate dental students. Methods and Materials: Forty-two undergraduate senior dental students participated in this study. The students experienced this course for the first time and were randomly divided into three groups (n=14). Group A attended live CD on a patient; group B watched a professionally produced demonstration video without any verbal explanation during 1 h; and finally group C watched the same video alongside live explanation by a mentor during the 1.5 h (VACID). The whole process was performed by an experienced endodontist on maxillary central incisors. All of The students carried out a multiple choice question exam to evaluate their comprehension. The mean score of the experimental groups were compared using ANOVA test and multiple comparisons were carried out with Tamhane test. The level of significance was set at 0.05. Results: There was significant difference among three groups according to the ANOVA test (P<0.05). Group VACID had the highest mean scores. There was significant difference between the groups VACID and VT (P=0.011); no significant differences were found in other inter-group comparisons. Conclusion: According to the results, VACID may improve the quality of endodontic training in undergraduate dental students. Keywords: Conventional Education; Endodontic Treatment; Knowledge; Performance; Video-Assisted Clinical Instruction